Pre-service teachers' reflections on content knowledge through microteaching. Issue 2 (4th March 2023) - Maguire, Kelly R.
ABSTRACT: Teacher preparation is an integral factor in education. Pre-service teachers do not have the same experience or content knowledge (CK) level as veteran teachers. Pre-service teachers must have opportunities to bolster their CK during teacher training. The purpose of this qualitative descriptive study was to explore how pre-service teachers described content knowledge using reflection-on-action after the planning, teaching, and feedback stages of microteaching. This study was theoretically supported by Schön's reflective practitioner model and guided by one research question. Purposive sampling was used to recruit 11 pre-service teachers who participated in microteaching sessions. Data were collected using semi-structured interviews. Four themes emerged from the data through thematic analysis: Pre-service teachers (1) rely on prior knowledge, (2) benefit from collaboration, (3) compensate when faced with unfamiliar content, (4) and feel microteaching validates content knowledge. Findings suggest that pre-service teachers benefit from engaging in reflection-on-action as a tool to facilitate the growth and development of content knowledge specific to their degree program and future teacher employment. This study recommends using reflection and microteaching with pre-service teachers in teacher training and future research.